Kajian Teknis Sistem Jaringan Ventilasi Tambang Ciurug Level 600 PT Aneka Tambang Tbk UBPE Pongkor - Leyriesa Awdina; Irvani Irvani; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2020)
According to field observation result the average dry temperature and wet temperature around between 23 – 30 ºC, with relative humidity around 83 - 93 % and contain 20.9 % O2, 4 ppm CO, on the front production there are 2 cross cut XC 636 and XC 644 have high temperature that reach 31 ºC and 100 % relative humidity. The acquired field data contain dry temperature, wet temperature, wet bulb global temperature, air velocity, and tunnel dimension so then effective temperature, work efficiency and work climate threshold value can be calculated. The result calculation get effective temperature is acquired 29 – 30 ºC, work efficiency 79 - 62 %, and climate threshold value with work arrangement as much 0 - 50 %. Technical problem on the field which causes high temperature is air recirculation from dirty air exhaust from XC 636 that is opposite with clean air direction from fan 75 kW, recirculation on access 644 from booster fan 37 kW located before XC 637 which results in increasing dirty air quantity into front production plus the second front with water puddles from drilling front roof droplets. Effort made on access XC 644 that is fan 75 kW replaced with fan 90 kW, and the tip of flexible duct extends after RC 7 so that the airflow doesn’t mix with exhaust from XC 636, aside from that booster fan 37 kW after XC 637 is moved so it help sucking dirty air from front XC 644, it can resolve air recirculation